Associação do COPD Assessment Test (CAT) com o eixo neuro-cardíaco na exacerbação grave em pacientes com Doença Pulmonar Obstrutiva Crônica - Sgarbosa, Nicole Marques (Universidade Federal de São Carlos, 2021)
Introduction: The patient with chronic obstructive pulmonary disease (COPD) often has exacerbations that culminate in hospitalizations. These events add a negative impact to COPD including changes in symptomatology and cardiac autonomic function. There is currently an interest in differentiating these patients into phenotypes using findings or a combination of common characteristics. However, it is not known whether patients who report a greater impact of the disease in this period have a worse profile in cardiac autonomic modulation (CAM). Objectives: To investigate whether in patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease (EACOPD), the impact of the referred disease influences the CAM. Methods: COPD patients of both sexes who were hospitalized for EADPOC were evaluated. The disease impact was assessed using the COPD Assessment Test (CAT) questionnaire, composed of 8 evaluative items on a scale from 0 to 5 with a final score of 0 to 40 points. The patients were divided into two groups: According to the values obtained in the CAT tool in 1) GCAT 1 (N = 11, patients with CAT≤20) and 2) GCAT 2 (N = 11, patients with CAT> 20). The evaluation of CAM was performed by analyzing the heart rate variability (HRV) considering the linear indications in the time domain (mean HR, mean RR, STDRR, rMSSD, RRtri, TINN) and in the frequency domain (LF, HF and LF/HF); and nonlinear analysis by Poincaré SD1, SD2, ApEn, SampEn, alpha1 and alpha 2) using a 300-point stretch in the heart rate record and RR interval in the dynamic process of HR at rest in patients hospitalized for EADPOC. Results: There were no significant differences between GCAT1 and GCAT2 (comparing HRV indications). There was a significant negative correlation between the SNS index and the CAT score (r =-0.44, p= 0.03). Positive correlations between CAT score and HRV variables: STDRR (r=0.54, p<0.01), RRtri (r=0.42, p=0.04), TINN (r=0.52, p=0.01), SD1 (r=0.50, p=0.01), SD2 (r=0.53, p=0.01). Conclusion: The clinical manifestation phenotypes during exacerbations of COPD do not differentiate the profile of autonomic cardiac modulation, however, it was observed that the greater the clinical impact of the disease, the greater the parasympathetic index and the total cardiac modulation.
Association of the COPD Assessment Test (CAT) and neuro-cardiac axis in severe exacerbation in patients with Chronic Obstructive Pulmonary Disease
Keywords: Doença pulmonar obstrutiva crônica; Exacerbação Aguda da Doença Pulmonar Obstrutiva Crônica; Controle autonômico cardíaco; Fenótipos; Chronic obstructive pulmonary disease; Acute Exacerbation of Chronic Obstructive Pulmonary Disease; Cardiac autonomic modulation; Phenotypes; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL